Systematic Review: The Effect of Gamification on Primary and Secondary Education Students - Galende Sánchez, Carlos (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2023)
The purpose of this article is to understand and identify the motivational aspects related to the use of gamified activities in the classroom, specifically in Primary and Secondary education stages. In this context, student motivation is a fundamental element in the teaching and learning process at any school level. In recent years, numerous authors have emphasized the importance of finding and applying teaching methodologies and strategies that enhance student motivation. Through this work, the main theoretical aspects underlying the study of emotions, motivation, and gamification have been identified. Additionally, a systematic review has been conducted to gather publications that provide scientific studies affirming the importance of working with gamified activities in the classroom. After analyzing the review results, a discussion has been carried out encompassing the relationship of this work with the subjects studied during the school year, as well as proposing future lines of work and addressing limitations encountered during the study. To conclude, a section of conclusions serves as a personal reflection and attempts to identify important aspects to consider for a better development of gamification regarding motivation